2015
DOI: 10.1371/journal.pone.0129566
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL-Based High Throughput Screening Reveals a Link between TRAIL-Mediated Apoptosis and Glutathione Reductase, a Key Component of Oxidative Stress Response

Abstract: A high throughput screen for compounds that induce TRAIL-mediated apoptosis identified ML100 as an active chemical probe, which potentiated TRAIL activity in prostate carcinoma PPC-1 and melanoma MDA-MB-435 cells. Follow-up in silico modeling and profiling in cell-based assays allowed us to identify NSC130362, pharmacophore analog of ML100 that induced 65-95% cytotoxicity in cancer cells and did not affect the viability of human primary hepatocytes. In agreement with the activation of the apoptotic pathway, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…Starting compounds should [1] elicit a reproducible response in at least two assay types and have a dose-response over a hundred-fold concentration range; [2] be analytically validated in terms of integrity and purity; [3] demonstrate adequate potency; [4] possess a tractable starting point of chemical optimization with no obvious major chemical liabilities. Most of these requirements were addressed in our previous publication [8]. Thus, we demonstrated that our lead compound, NSC130362 (Fig 1, A) selectively induces reproducible responses in either oxidative stress or caspase 3/7 activity assays in cancer cells.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…Starting compounds should [1] elicit a reproducible response in at least two assay types and have a dose-response over a hundred-fold concentration range; [2] be analytically validated in terms of integrity and purity; [3] demonstrate adequate potency; [4] possess a tractable starting point of chemical optimization with no obvious major chemical liabilities. Most of these requirements were addressed in our previous publication [8]. Thus, we demonstrated that our lead compound, NSC130362 (Fig 1, A) selectively induces reproducible responses in either oxidative stress or caspase 3/7 activity assays in cancer cells.…”
Section: Resultsmentioning
confidence: 68%
“…Elevated levels of reactive oxygen species (ROS) and subsequent oxidative stress are hallmarks of carcinogenesis and metastasis providing a potential therapeutic index [24]. Our data and recent studies by others demonstrated that elevated levels of ROS can be exploited in vitro and in vivo to preferentially target cancer cells while sparing normal cells [58]. The ROS-based approach to induce apoptosis in cancer cells is conceptionally different from conventional therapy targeting well known oncogenes and tumor suppressors - a therapy which is often ineffective due to multiple genetic and epigenetic alterations in cancer cells and the ability of cancer cells to upregulate compensatory mechanisms [9, 10].…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations